True random coded photon counting Lidar - Liu Bo (Institue of Optics and Electronics, Chinese Academy of Sciences, 2020)
A true random coded photon counting Lidar system is proposed in this paper, in which a single photon detector acts as the true random sequence signal generator instead of the traditional function generator. Compared with the traditional pseudo-random coded method, the true random coded method not only improves the anti-crosstalk capability of the system, but more importantly, it effectively overcomes the adverse effect of the detector's dead time on the ranging performance. The experiment results show that the ranging performance of the true random coded method is obviously better than that of the pseudo-random coded method. As a result, a three-dimensional scanning imaging of a model car is completed by the true random coded method.